Chemistry Learning Outcomes Assessment: How is The Quality of The Tests Made by The Teacher? - Rizki Nor Amelia; Anggi Ristiyana Puspita Sari; Sri Rejeki Dwi Astuti (Journal of Educational Chemistry (JEC), 2021)
The teacher-made chemistry test must have a good quality, due to the decision taken from the tests has an impact on the students. Therefore, the purpose of the research is to explore the quality of teacher-made chemistry tests such as item fit and person fit, item difficulty, and test reliability. The sample consisted of 356 senior students from senior high schools in Yogyakarta that were selected by cluster random sampling technique. The research used the teacher-made chemistry test consisted of 40 multiple choice items which were collected using documentation technique. Data were analyzed with Rasch Model using Winsteps 3.73 version. The result showed that all items in the teacher-made chemical test were proven to have good quality (fit model, good item difficulty, and good test reliability). Moreover, 18 students were identified as misfit persons. From the findings, the test can be used to assess the students’ learning outcomes, especially for the try-out of the final exam in senior high school. Besides, the students identified as person misfits should be further examined and receive teachers’ guidance.